ANALISIS TENTANG EFEKTIVITAS SISTEM PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN DI SMPIT AL-FIKRI ISLAMIC GREEN SCHOOL PEKANBARU - Rahmatullaila, Fitri; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the effectiveness of the online learning system on student learning outcomes in Civics subjects at SMPIT Al-Fikri Islamic Green school Pekanbaru. The formulation of the problem in this study is how the effectiveness of the online learning system on student learning outcomes in Civics subjects at SMPIT Al-Fikri Islamic Green School Pekanbaru. The purpose of the study was to find out how the effectiveness of the online learning system on student learning outcomes in Civics subjects at SMPIT Al-Fikri Islamic Green School Pekanbaru students of SMPIT Al-Fikri Islamic Green School Pekanbaru who were taking Civics subjects and totaled 92 students. The research sample amounted to 47 students who were students and students of class VII & VIII determined by purposive sampling technique. The type of research used is descriptive quantitative with the measuring instrument used for each variable is a questionnaire and documentation where the data obtained is processed with the SPSS version 16 application. equal to 0.585 Then it can be concluded that in this case Fcount is smaller than Ftable, then Ho is accepted. So that there is no significant effectiveness between the online learning system on student learning outcomes at SMPIT Al-Fikri Islamic Green School Pekanbaru. Based on this statement, the research hypothesis is rejected. the coefficient of determination (R Square) is 0.013 which implies that the effect of the independent variable (Online Learning System Effectiveness) on the dependent variable (Student Learning Outcomes) is 11.3%. While 88.7% (100% -11.3%) is influenced by other variables not examined in this study.Key Words: Effectiveness, Online Learning, Student Learning Outcomes